2020
DOI: 10.1098/rspb.2020.1265
|View full text |Cite
|
Sign up to set email alerts
|

Do novel insecticides pose a threat to beneficial insects?

Abstract: Systemic insecticides, such as neonicotinoids, are a major contributor towards beneficial insect declines. This has led to bans and restrictions on neonicotinoid use globally, most noticeably in the European Union, where four commonly used neonicotinoids (imidacloprid, thiamethoxam, clothianidin and thiacloprid) are banned from outside agricultural use. While this might seem like a victory for conservation, restrictions on neonicotinoid use will only benefit insect populations if newly emerging insecticides do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(103 citation statements)
references
References 102 publications
0
89
0
Order By: Relevance
“…Flupyradifurone (FPF) (Sivanto™) is a newly developed systemic insecticide as an alternative to neonicotinoids. Although it has been declared that FPF has a favorable safety profile for honey bees and other pollinators, a meta-analysis of systematic literature studies of potential sub-lethal effects of FPF has demonstrated that exposure to field-realistic levels of FPF exhibited significant sub-lethal impacts on honey bees [ 39 ]. This study investigated the effects of FPF on the development on larvae as well as foraging ability of foragers who consume the syrup during exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Flupyradifurone (FPF) (Sivanto™) is a newly developed systemic insecticide as an alternative to neonicotinoids. Although it has been declared that FPF has a favorable safety profile for honey bees and other pollinators, a meta-analysis of systematic literature studies of potential sub-lethal effects of FPF has demonstrated that exposure to field-realistic levels of FPF exhibited significant sub-lethal impacts on honey bees [ 39 ]. This study investigated the effects of FPF on the development on larvae as well as foraging ability of foragers who consume the syrup during exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Seed treatments replacing neonicotinoids are currently entering the market in the EU 38 . In 2020 in Sweden, a limited quantity of winter oilseed rape was seed‐treated with the systemic insecticide flupyradifurone.…”
Section: Perspective and International Outlookmentioning
confidence: 99%
“…In 2020 in Sweden, a limited quantity of winter oilseed rape was seed‐treated with the systemic insecticide flupyradifurone. Negative effects of these new compounds on beneficial insects have, however, already been reported, 38 making their future regulatory status uncertain. Future strategies for crop protection against insect pests in oilseed rape in the EU should therefore be prepared for a situation in which insecticides will be limited in their availability 25 …”
Section: Perspective and International Outlookmentioning
confidence: 99%
“…The classical approach of combatting agricultural insect pests is via non-selective conventional insecticides. However, their limited target species selectivity has serious disadvantages, including a detrimental impact on environment and human health [ 229 , 230 , 231 , 232 ]. In fact, these concerns are increasing and have led to a ban in some commonly used insecticides [ 233 , 234 , 235 ].…”
Section: Biotechnological Prospectsmentioning
confidence: 99%